A descriptive study of 10-year clozapine use from the nationwide database in Japan. (March 2021) - Toyoda, Katsunori; Hata, Takeo; Yamauchi, Shigeru; Kinoshita, Shinya; Nishihara, Masami; Uchiyama, Kazuhisa; Inada, Ken; Kanazawa, Tetsufumi
Highlight: We have surveyed the data obtained from national database of Clozaril® Patient Monitoring Service in Japan. The derived data are comprised of 8, 263 patients for whom clozapine was actually prescribed. Clozapine became available in Japan from 2009, however there was a clear increase in the number of patients from January 2016. There was a difference in the mean dosage used during treatment (Early observation group: 309.1 mg vs Late observation group: 247.9 mg). The discontinuation rate due to granulocytopenia was significantly lower in the late observation group. In the future, to further effectively use clozapine, indication criteria for clozapine and regulations for blood testing intervals must be assessed using clinical data. Abstract: This survey was conducted to identify the actual usage of clozapine and changes required to increase the number of patients with schizophrenia who would benefit from clozapine. We obtained Clozaril® Patient Monitoring Service (CPMS) data for 8, 263 patients that received clozapine between July 2009 and January 2020. Patients were divided into the early ( n =3, 696 cases, which have been analyzed previously) and late groups ( n =4, 567 cases) according to the date of the treatment initiation. In total, 417 facilities offered the drug, with a surge in cases in the late group (40.0 hospitals/year, 568.6 cases/year vs. 39.3 hospitals/year, 1, 141.8 cases/year). We found a significant between-group difference in the mean dosage during treatment (early group: 309.1 mg/day; late group: 247.9 mg/day). The treatment continuation rates at 1 and 4 years in all study participants were 77.2% and 65.1%, respectively. The incidences of granulocytopenia and agranulocytosis were 5.5% and 1.0%, respectively. The discontinuation rate because of granulocytopenia was significantly lower in the late group. There were no differences in the discontinuation rate because of glucose intolerance between the groups. An assessment of the current CPMS regulations may be required to further examine the clozapine use effectiveness.